O ciclo de aprendizagem experiencial como suporte para a aprendizagem significativa de termologia no 9º ano do ensino fundamental - Giaretta, Pedro Henrique (2020)
The present study is based on the observation that Physics teaching in contemporary education is still outdated regarding to educational aims. Subjects such as thermology are presented, in general, under very distant aspects from the students’ daily lives and the teaching is focused on the contents transmission in an expositive way. In addition, due to the insufficient training that teachers have received, they do not feel prepared to elaborate or use new methodologies. Since they do not have sufficient subsidies, teachers need alternatives in order to develop new educational methodologies. Considering this necessity, this dissertation, inserted in the research line “Educational Practices in Science and Mathematics Teaching”, sought subsidies in the Meaningful Learning Theory (MLT), by David Paul Ausubel, and in the Experiential Learning Cycle (ELC), methodology proposed by David Allen Kolb in order to answer the guiding research question: how the Experiential Learning Cycle can serve as methodological support to promote thermology meaningful learning for elementary school 9th grade students? Therefore, the aim of these study is to identify evidence of thermology significant learning in the 9th grade of elementary school through the use of the ELC. In order to achieve this aim, a didactic sequence was elaborated to approach the basic concepts of thermology, it is based on the MLT fundamentals and is comprised of two cycles that contemplate the four stages proposed by Kolb. The didactic sequence was structured in nine meetings and developed in a private school in Passo Fundo, RS. Grounded in a qualitative and participant nature, the research is focused on identifying signs of significant learning from four analysis categories: i) identification of subsumer concepts, ii) evidence of the willingness to learn, iii) progressive differentiation and integrative reconciliation of concepts and iv) application of the concepts studied in different contexts from those addressed in the didactic sequence development. The proposal was evaluated through two instruments: the researcher logbook and the materials produced by the participants. The collected data analysis allows to point out the proposal feasibility and the importance of methodologies based on bringing the contents closer to the knowledge that the students already have. In addition, the study highlighted the relevance of knowing and using new proposals that represent benefits for the promotion of meaningful learning. Finally, it is highlighted that new methodologies need to be shared in order to a greater number of teachers can get to know them and, from them, develop new teaching practices. Based on this perspective, the study gave rise to a support material for teachers, which consists this dissertation educational product, made available at